Optimization of Normal Concrete Mixture with the Addition of Fiberglass and Rice Husk Ash - Manginsihi, Barakati Karel; Kondoj, Noldie E.; Rasjid, Efendy; Pangemanan, Syanne; Kabo, Don R. G. (Jurnal Multidisiplin Madani, 2023)
This study aims to determine the effect of using fiberglass and rice husk ash waste in making normal concrete. The variations of fiberglass used are 0%, 0.2%, 0.4%, and 0.6% of the weight of cement, while the variations of rice husk ash waste used as a partial replacement of cement are 0%, 5%, 10%, and 15%. Testing was carried out on concrete for ages of 7, 14, and 28 days, focusing on the compressive strength and flexural strength of concrete.This research was conducted at the Material Testing Laboratory of the Civil Engineering Department of the Manado State Polytechnic, with a research period of four months and the methods used were experimental and data analysis.The results of this study indicate that the addition of fiberglass fibers increases the compressive strength of concrete, while the use of rice husk ash waste as a partial replacement of cement shows varying effects on the compressive strength value, with a decrease in the higher percentage of rice husk ash. The optimal combination of 0.6% fiberglass and 5% rice husk ash provides an increase in the flexural strength of concrete where the flexural strength for 14 days is 2.99 Mpa, and the concrete age of 28 days is 3.36 MPa. This study provides insight into the potential use of alternative materials to improve the quality and sustainability of concrete construction.